Genotoxicity of Particles From Grinded Plastic Items in Caco-2 and HepG2 Cells - Roursgaard, Martin; Hezareh Rothmann, Monika; Schulte, Juliane; Karadimou, Ioanna; Marinelli, Elena; Møller, Peter (Frontiers in Public Health, 2022)
Large plastic litters degrade in the environment to micro- and nanoplastics, which may then enter the food chain and lead to human exposure by ingestion. The present study explored ways to obtain nanoplastic particles from real-life food containers. The first set of experiments gave rise to polypropylene nanoplastic suspensions with a hydrodynamic particle size range between 100 and 600 nm, whereas the same grinding process of polyethylene terephthalate (PET) produced suspensions of particles with a primary size between 100 and 300 nm. The exposure did not cause cytotoxicity measured by the lactate dehydrogenase (LDH) and water soluble tetrazolium 1 (WST-1) assays in Caco-2 and HepG2 cells. Nanoplastics of transparent PET food containers produced a modest concentration-dependent increase in DNA strand breaks, measured by the alkaline comet assay [net induction of 0.28 lesions/106 bp at the highest concentration (95% CI: 0.04; 0.51 lesions/106 base pair)]. The exposure to nanoplastics from transparent polypropylene food containers was also positively associated with DNA strand breaks [i.e., net induction of 0.10 lesions/106 base pair (95% CI: −0.04; 0.23 lesions/106 base pair)] at the highest concentration. Nanoplastics from grinding of black colored PET food containers demonstrated no effect on HepG2 and Caco-2 cells in terms of cytotoxicity, reactive oxygen species production or changes in cell cycle distribution. The net induction of DNA strand breaks was 0.43 lesions/106 bp (95% CI: 0.09; 0.78 lesions/106 bp) at the highest concentration of nanoplastics from black PET food containers. Collectively, the results indicate that exposure to nanoplastics from real-life consumer products can cause genotoxicity in cell cultures.